The Effect Of Drawing Program in Fostering On Hope with Attempted Suicide Patients - แจ้งสันเทีย ปัทพร; แนบเกษร ชนัดดา (Journal of The Royal Thai Army Nurses, 2018)
Fostering hope in attempted suicide patients. is to promote positive power and resilience in order to establish hope for conduct of life in the future. This quasi-experimental study is to examine the effect of fostering hope by drawing therapy on hope in attempted suicide patients. Twenty participants from Wichainburi hospital, were recruited by inclusion criteria and were randomly into experimental group and control group equally. This drawing therapy developed Human Care Theory, Herth hope concept art model. The experimental group received 90-120 minutes in 5 session, while those in the control group received routine nursing care. The hope scale was employed to evaluate pre-posttest and one month follow-up. Descriptive statistics, independent t-test, two way repeated measure ANOVA and multiple comparison test by Bonferroni method were employed to analyze the data. The results demonstrated that the mean scores of hope between experimental group and control group at post-test and 1 month follow-up were significantly different at .05 In experimental group, mean score of hope at pre-test, post-test and one-month follow-up were significantly different at .05 From post-hoc comparison, there were significantly different at .05 between mean scores at post-test and one-month follow-up period. The results suggest that nurses and health care providers could apply this drawing therapy for increasing hope in attempted suicide patients.